A rare case of Leiomyosarcoma of the Prostate presenting with Recurrent Hematuria and Retention of Urine - Shafiquzzaman, Md; Rahman, Md Habibur; Hossain, Tohid Mohammad Saiful; Hossain, Md Shamim; Chakravarty, Saumitra; Islam, Md Serajul (Bangladesh Journal of Urology, 2023)
Leiomyosarcoma of the prostate is an extremely rare aggressive tumor accounting for only 0.1-0.2% of all malignant prostatic tumors. About two hundred cases have been reported worldwide in the literature so far. There are no specific clinical features and imaging characteristics that can detect the condition, rather it is a histopathological and immunohistochemical diagnosis. So, a high degree of skepticism is needed in patients with hematuria, obstructive lower urinary tract symptoms with normal serum prostate specific antigen to detect the condition in time. Though there is no certain treatment modality for this condition, a multidisciplinary approach and aggressive management may benefit the patient. Here we report a case presented with recurrent episodes of hematuria, retention of urine and a history of transurethral resection of prostate multiple times which revealed benign prostatic hyperplasia. We have performed radical cystoprostatectomy of this patient which revealed Leiomyosarcoma of the Prostate. The patient was referred to clinical oncology for further management. But unfortunately, the patient died before receiving any systemic therapy. Bangladesh J. Urol. 2023; 26(1): 52-57